Blessed souls and diabolical pacts: A platonic scolding to Santander’s drunkards and idolaters from prose mythology - Caballero Hernández, Farouk (Rastros Rostros, 2012)
This work of reflection was conducted at the Universidad de los Andes in 2011 in the research line “Oral mythological tradition”.It studies Pedro Gómez Valderrama in his only novel,La otra raya del tigre (The tiger’s other strip), and Enrique Otero D’Costa in his two tales about blessed souls. In these three stories, prose mythology educates people on their work and Christian responsibilities, while it censors the habit of drinking. The works make a scolding in order to promote morality and good practices.
Keywords: discourse and story; hegemony; mythology; morality